microRNAs in nociceptive circuits as predictors of future clinical applications - Kress, Michaela; Hüttenhofer, Alexander; Landry, Marc; Kuner, Rohini; Favereaux, Alexandre; Greenberg, David S.; Bednarik, Josef; Heppenstall, Paul; Kronenberg, Florian; Malcangio, Marzia; Rittner, Heike; Üçeyler, Nurcan; et al. (Frontiers in Molecular Neuroscience, 2013)
Neuro-immune alterations in the peripheral and central nervous system play a role in the pathophysiology of chronic pain, and non-coding RNAs (ncRNAs) – and microRNAs (miRNAs) in particular - regulate both immune and neuronal processes. Specifically, miRNAs control macromolecular complexes in neurons, glia and immune cells and regulate signals used for neuro-immune communication in the pain pathway. Therefore, miRNAs may be hypothesised as critically important master switches modulating chronic pain. In particular, understanding the concerted function of miRNA in the regulation of nociception and endogenous analgesia and defining the importance of miRNAs in the circuitries and cognitive, emotional and behavioural components involved in pain is expected to shed new light on the enigmatic pathophysiology of neuropathic pain, migraine and complex regional pain syndrome (CRPS). Specific miRNAs may evolve as new druggable molecular targets for pain prevention and relief. Furthermore, predisposing miRNA expression patterns and inter-individual variations and polymorphisms in miRNAs and/or their binding sites may serve as biomarkers for pain and help to predict individual risks for certain types of pain and responsiveness to analgesic drugs. miRNA-based diagnostics are expected to develop into hands-on tools that allow better patient stratification, improved mechanism-based treatment, and targeted prevention strategies for high risk individuals.